Part a
Use (x + 5, -y) for the input.
(5, 3) becomes (5 + 5, -3) = (10, -3).
Part b
Use the same rule.
(-2, 7) becomes (-2 + 5, -7) = (3, -7).
Done.
Part a)
The output is: (10,-3)
Part b)
The output is: (3,-7)
The rule which is used to transform is:
(x,y) → (x + 5, - y)
This means that the x-coordinate is shifted 5 units to the right and the y coordinate is negated.
If we give the input as: (5,3)
Then the output will be:
(5,3) → (5+5,-3)
i.e.
(5,3) → (10,-3)
Now, again when we input the value as: (-2,7)
(-2,7) → ( -2+5,-7)
(-2,7) → (3,-7)
5.7m questions
7.5m answers